Combined morphological and phylogenomic re-examination of malawimonads, a critical taxon for inferring the evolutionary history of eukaryotes - Heiss, Aaron A; Kolisko, Martin; Ekelund, Fleming; Brown, Matthew W; Roger, Andrew J; Simpson, Alastair G B (Royal Society open science, 2018)
Modern syntheses of eukaryote diversity assign almost all taxa to one of three groups: Amorphea, Diaphoretickes and Excavata (comprising Discoba and Metamonada). The most glaring exception is Malawimonadidae, a group of small heterotrophic flagellates that resemble Excavata by morphology, but branch with Amorphea in most phylogenomic analyses. However, just one malawimonad, Malawimonas jakobiformis, has been studied with both morphological and molecular-phylogenetic approaches, raising the spectre of interpretation errors and phylogenetic artefacts from low taxon sampling. We report a morphological and phylogenomic study of a new deep-branching malawimonad, Gefionella okellyi n. gen. n. sp. Electron microscopy revealed all canonical features of 'typical excavates', including flagellar vanes (as an opposed pair, unlike M. jakobiformis but like many metamonads) and a composite fibre. Initial phylogenomic analyses grouped malawimonads with the Amorphea-related orphan lineage Collodictyon, separate from a Metamonada+Discoba clade. However, support for this topology weakened when more sophisticated evolutionary models were used, and/or fast-evolving sites and long-branching taxa (FS/LB) were excluded. Analyses of '-FS/LB' datasets instead suggested a relationship between malawimonads and metamonads. The 'malawimonad+metamonad signal' in morphological and molecular data argues against a strict Metamonada+Discoba clade (i.e. the predominant concept of Excavata). A Metamonad+Discoba clade should therefore not be assumed when inferring deep-level evolutionary history in eukaryotes.
Keywords: Excavata; ultrastructure; protist; Metamonada; eukaryote evolution; transcriptomics